Solar light emitting diode (LED) street lighting with automatic vehicle detection system - Wan Mohd Faizal Wan Nik (School of Electrical Power Engineering, University Malaysia Perlis, 2014)
This thesis is about a development and fabrication of solar light emitting diode (LED) street lighting with an automatic vehicle detection system. The project comprises of the development of the DC to DC boost converter, dark and vehicle detection sensor and LED lamp driver. The boost converter system was designed to overcome the problem due to the lower output voltage from the solar panel compare to the optimum level of batteries charging voltage.